2016
DOI: 10.1016/j.marpolbul.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation as a ballast water treatment strategy: Inactivation of phytoplankton measured with flow cytometry

Abstract: This study investigates different UV doses (mJ/cm(2)) and the effect of dark incubation on the survival of the algae Tetraselmis suecica, to simulate ballast water treatment and subsequent transport. Samples were UV irradiated and analyzed by flow cytometry and standard culturing methods. Doses of ≥400 mJ/cm(2) rendered inactivation after 1 day as measured by all analytical methods, and are recommended for ballast water treatment if immediate impairment is required. Irradiation with lower UV doses (100-200 mJ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
3
22
0
1
Order By: Relevance
“…The lowest UV dose is comparable to those used in BWTS, but ballast water is treated twice (on uptake and discharge). UV doses between 400 and 800 mJ cm −2 were not applied, since previous FCM studies showed that CFDA-AM-stained T. suecica UV irradiated with 400 mJ cm −2 were permanently inactivated (Olsen et al 2016). Doses of 400 and 800 mJ cm −2 were both included in the study to examine whether and how esterase activity and membrane integrity differed in these samples.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The lowest UV dose is comparable to those used in BWTS, but ballast water is treated twice (on uptake and discharge). UV doses between 400 and 800 mJ cm −2 were not applied, since previous FCM studies showed that CFDA-AM-stained T. suecica UV irradiated with 400 mJ cm −2 were permanently inactivated (Olsen et al 2016). Doses of 400 and 800 mJ cm −2 were both included in the study to examine whether and how esterase activity and membrane integrity differed in these samples.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Many research studies have been undertaken in the search for effective approaches to treat contaminated water. Mori et al [6] and Olsen et al [7] suggested an ultra violet lightemitting diode (UV-LED) device as an effective method to sterilize water. Sinclair et al [8] conducted water sterilization using cellulose membrane filters grafted with silver nanoparticles and nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the dose requirements depends on the treatment context, as it may require lower doses if the treatment is applied during the ballasting and then followed by a light-limited period, or higher doses if immediate impairment is necessary, in case of the treatment during the ballast discharge (Olsen et al 2016). The survivorship of phytoplankton organisms such as Tisochrysis lutea (formerly known as Isochrysis galbana, T-ISO; Bendif et al 2013) presents a clear response to UV irradiation, and their adequate growth rate, obvious degradation of nonviable organisms, ease and stability in culturing and wide commercial availability constitute a consistent basis for developing a normalized protocol to determine the inactivating effect of UV-based treatments.…”
Section: Introductionmentioning
confidence: 99%